2019
DOI: 10.1111/bjd.18601
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐country generalizability of quality‐of‐life scores in atopic dermatitis

Abstract: Linked Article: Andersen et al. Br J Dermatol 2020; 182:1176–1183.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…AD can significantly impact patients’ ability to work, indicating that indirect costs associated with AD may be substantial [ 16 ]. A comprehensive European study found that 57% of patients with AD missed at least one day of work in the previous year due to their skin condition [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…AD can significantly impact patients’ ability to work, indicating that indirect costs associated with AD may be substantial [ 16 ]. A comprehensive European study found that 57% of patients with AD missed at least one day of work in the previous year due to their skin condition [ 17 ].…”
Section: Introductionmentioning
confidence: 99%